"Snow days are the best days." Exploring Teachers’ and Administrators’ Perceptions of Weather-Related School Disruptions - Button, Brenton; Ouellette, Carson; Martin, Gina (Alberta Journal of Educational Research, 2024)
Extreme weather events are becoming increasingly common and have the potential to impact the school day. This study aimed to explore teachers’ and administrators’ perspectives on weather-related school closures. Semi-structured interviews were conducted with ten key informants and analyzed using content analysis. Informants took a strengths-based approach and discussed the benefits of weather-related disruptions for student mental health and planning time. However, informants did mention that if these days continued to rise, it might be a cause for concern. School boards need to begin monitoring the impact of weather events. Les phénomènes météorologiques extrêmes sont de plus en plus fréquents et peuvent avoir une incidence sur la journée scolaire. Cette étude visait à explorer les perspectives des enseignants et des administrateurs sur les fermetures d'écoles liées aux conditions météorologiques. Des entrevues semi-structurées ont été menées avec dix informateurs clés et analysés à l'aide d'une analyse de contenu. Les informateurs ont adopté une approche fondée sur les points forts et ont discuté des avantages des perturbations liées aux conditions météorologiques pour la santé mentale des élèves et le temps de planification. Cependant, les informateurs ont mentionné que si ces jours continuaient à augmenter, cela pourrait être une source d'inquiétude. Les conseils scolaires doivent commencer à surveiller l'incidence des événements météorologiques.